Leptospiral TlyC is an extracellular matrix-binding protein and does not present hemolysin activity - Carvalho, Eneas (2009)
The role of TlyA, TlyB and TlyC proteins in the biology of Leptospira is still uncertain. Although these proteins have been considered as putative hemolysins, we demonstrate that leptospiral recombinant TlyB and TlyC do not possess hemolytic activity. However, further experiments showed that TlyC is a surface-exposed protein that seems to bind to laminin, collagen IV and fibronectin. The expression of both proteins was detected both in vitro and in vivo. Our findings suggest that TlyB and TlyC are not directly involved in hemolysis, and that TlyC may contribute to Leptospira binding to extracellular matrix (ECM) during host infection.